The Relationship Between Maternal Weight Gain During Pregnancy and Compliance with Antenatal Care and Baby's Weight at Birth - Fitria Nur Kusuma; Shinta Riana; Tri Agustina; Erna Herawati (Eduvest - Journal of Universal Studies, 2024)
Newborn baby weight is an indicator of baby health because it is important to determine infant mortality and morbidity as well as the quality of human resources. One of the factors causing LBW is low weight gain during pregnancy. Objective: To determine the relationship between weight gain in pregnant women and ANC compliance with the baby's weight at birth. Method: Using analytical observational designcross-sectional with a purposive sampling technique. Results: The total sample is 100 respondents. The results of the bivariate test between the weight gain of pregnant women and the baby's weight at birth showed a p value of 0.001 (p < 0.05), withThe prevalence ratio (RP) was found to be 5.038with 95% CI 4.333 – 43.873. And the relationship between ANC compliance and the baby's weight at birth was found to have a p value of 0.001 (p < 0.05)with a Prevalence Ratio (RP) obtained at 4.444with 95% CI 2.580 – 24.122. The results of the multivariate test of the relationship between the increase in pregnant women's weight and the baby's weight at birth showed an OR value of 12.016 with a 95% CI value of 3.470 - 41.607, and the relationship between ANC compliance and the baby's weight at birth obtained an OR value of 6.480 with a 95% CI 1.757 - 23.899. Conclusion: There is a relationship between the weight gain of pregnant women and ANC compliance with the baby's weight at birth.The increase in weight of mothers during pregnancy is more influential.